USING HELIOSPHERE LEARNING MEDIA TO MOTIVATE ELEMENTARY SCHOOL STUDENTS - Putri Zudhah Ferryka; Abinda Nova Aulia; Adinda Putri Sabila , dkk; Ainun Nadia; Alfina Sukma (El Midad, 2025)
This study aims to use heliosphere media to increase the learning motivation of SDN 3 Ketan's grade VI science students. Sixteen students are the subjects of the classroom action research (CAR) methodology. Questionnaires, documentation, interviews, and observation were used to gather data and subjected to qualitative descriptive analysis. The study's findings demonstrated that Heliosphere successfully raised pupils' motivation for learning. According to observations and survey results, up to 75% of students reported feeling more motivated after using this medium for studying. In conclusion, heliosphere media can be valuable for raising primary school pupils' motivation to learn science